Communicating With Confidence in the AI Era: Enhancing Professional English Competency and Literacy for Journalists in Pontianak Post - Eka Ariyati; Aunurrahman; Urai Salam; Haratua Tiur Marta; Muhammad Basri; Venny Karolina; Farina Nozakiah Tazijan; Siti Fauziana Zakaria; Abdul Azim Mahda; Aiman Zulaikha Mohd; Novantar Ramses Negara; Qonita Indah Arrusli (Unram Journal of Community Service, 2025)
This article reports on a community service program conducted by FKIP Universitas Tanjungpura in collaboration with Universiti Teknologi MARA (UiTM) Malaysia, aimed at enhancing professional English competency and AI literacy among journalists at Pontianak Post. The program integrated comprehensive English communication training with artificial intelligence tool applications, including ChatGPT, Google AI Studio, Elicit, Consensus, Humata, Otter AI, and Canva AI. A post-training survey was administered to 20 participating journalists using a Likert-scale instrument supplemented by open-ended questions. Results indicate overwhelmingly positive outcomes, with overall satisfaction reaching 4.80 out of 5.00. The highest-rated aspects included the international collaboration value (4.85), AI-enhanced learning effectiveness (4.80), and participants' intention to continue using AI tools in their professional practice (4.80). Qualitative feedback revealed that journalists experienced significant improvements in their confidence to communicate in English, enhanced efficiency in news production through AI integration, and increased awareness of ethical considerations in technology-assisted journalism. The findings demonstrate that combining language competency training with digital literacy creates a synergistic effect that prepares journalists for the evolving demands of contemporary media practice.